Permainan Bahasa: “Apa dan Siapa” - Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The existence of language can be “tricked” by speakers in accordance with the purpose of the message content, so it would be created a form of “the language games” .On methods, the article writing is based on three stages: data collection, classification and data analysis, and writing stages. The purpose of writing is the search for answering to “What is “the language games” and “Who is “a language creator”. Based on the fact that communication with the form of “the language games” parallel to common communication, because both are strategic and functional. Thus, the existence of the form of “the language games” are interesting studied depthly, because its regarded as a linguistic phenomenon of its own.